Budidaya Maggot BSF Sebagai Pakan Unggas Dan Potensi Pemasaran Pada Karang Taruna Desa Ponain - Sabat, Diana; Setyani, Ni Made Paramita; Sol’uf, Morin M.; Mulik, Simon E.; Ndun, Alberth N.; Lawa@gmail.com, Alvrado B.; Nguru, David A.; Padu, Hendrikus U.; Nifu, Salden E. (Lembaga Dongan Dosen, 2024)
This Community Service (PKM) aims to to improve the knowledge and skills of the Ponain Village community, Amarasi District, Kupang Regency, in the cultivation of Black Soldier Fly (BSF) maggot and agricultural waste management. (BSF) maggot cultivation and agricultural waste management. Through lectures, discussions, and demonstrations, this activity involved 25 members of Karang Taruna as participants. The evaluation results showed significant improvements in various aspects: understanding of the material increased from 60% to 80%, practical skills from 50% to 90%, and understanding of product marketing from 40% to 80%. The level of participation rate reached 100%, and there was a strong commitment to continue maggot cultivation and waste management. continue maggot cultivation and waste management. These results show that PKM is effective in empowering communities, increasing productivity, and opening new economic opportunities. Recommendations for future activities include further counselling and more intensive mentoring to ensure the sustainability of the programme.